2013
DOI: 10.1371/journal.pone.0058571
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Design of Fragment Mixtures for NMR-Based Screening

Abstract: Fragment-based drug discovery is widely applied both in industrial and in academic screening programs. Several screening techniques rely on NMR to detect binding of a fragment to a target. NMR-based methods are among the most sensitive techniques and have the further advantage of yielding a low rate of false positives and negatives. However, NMR is intrinsically slower than other screening techniques; thus, to increase throughput in NMR-based screening, researchers often assay mixtures of fragments, rather tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…These statistics are not surprising because the BMRB virtual library consists of mostly small metabolites. Such a high density of aliphatic peaks may reasonably be expected to provide a challenge toward creating mixtures with nonoverlapped peaks; however, a previous analysis indicated that library size and peak distribution do not appear to significantly affect the results of optimization by simulated annealing, 10 and this expectation was confirmed by the results of NMRmix shown below.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…These statistics are not surprising because the BMRB virtual library consists of mostly small metabolites. Such a high density of aliphatic peaks may reasonably be expected to provide a challenge toward creating mixtures with nonoverlapped peaks; however, a previous analysis indicated that library size and peak distribution do not appear to significantly affect the results of optimization by simulated annealing, 10 and this expectation was confirmed by the results of NMRmix shown below.…”
Section: Resultsmentioning
confidence: 85%
“…The optimization of mixtures is accomplished by using a simulated annealing algorithm previously described. 10 The user-friendly GUI facilitates easy mixture optimization and data analysis, and NMRmix only requires information about the compound library and a source for reference 1D 1 H peak lists to get started. Additionally, NMRmix introduces the concept of intensity scoring, which penalizes overlaps that occur on the most intense peaks instead of treating overlaps of all peaks equally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pooling was performed based on predicted non-overlapping chemical shifts using the NMR prediction algorithms implemented in the Perch software (Perch Solutions). Briefly, a Monte Carlo algorithm was implemented to minimize NMR signal overlap [29]. The threshold for pairwise peak overlap, i.e., minimum distance between non-overlapping peaks, was set at 0.1 ppm.…”
Section: Pooling For Nmr Screenmentioning
confidence: 99%
“…To speed up the fragment screening, ap reviouslyd escribed computational approach [68] was used to group compounds into cocktails that have minimized NMR signal overlap.T his approach translates the NMR spectra of each compound into ac omputer-readablef ormat (fingerprint) and then minimizes the globals ignal overlap by aS A( Monte-Carlo-Metropolis) algorithm. Using this algorithm, 81 five-fragmentm ixtures, containingatotal of 402 compounds,w erep repared.…”
Section: Screening Of Fragment-based Librariesmentioning
confidence: 99%